A performance‐based indicator chemical framework for potable reuse. Issue 5 (5th October 2020) - Thompson, Kyle A.; Dickenson, Eric R. V.
Abstract: Many organic chemicals occur in reclaimed water at higher concentrations than in conventional drinking water sources. Some of these chemicals are known to occur at concentrations that pose chronic health risks. The toxicity or occurrence of other chemicals may not yet be known. Thus, potable reuse systems should achieve robust removal of known and unknown chemicals to ensure public health protection. Here, criteria were proposed for performance‐based indicators that could cost‐effectively verify this robust removal. The selection process was then demonstrated for a hypothetical system using ozonation, granular activated carbon, and direct ultraviolet photolysis. A set of indicators (e.g., acesulfame, meprobamate, perfluoroheptanoic acid, sucralose, iopromide, benzotriazole, and iohexol) was recommended on the basis of original and literature review data. However, the concentrations of some of these indicators are sufficient at certain locations only or decrease over time. Thus, indicators should be site‐specific, periodically reevaluated, and the topic of further research.